THE PATHWAY BETWEEN HYALOID BLOOD AND RETINAL NEURONS IN THE TOAD : Structural Observations and Permeability to Tracer Substances - Lasansky, Arnaldo (The Rockefeller University Press, 1967)
The hyaloid vessels form a capillary network on the inner surface of the retina. These capillaries are embedded in the vitreous humor, and they lack a glial investment. The intercellular spaces of the retina communicate with the ocular cavity, as can be evidenced by following the penetration of tracer substances. Hence, there is an extracellular diffusion pathway between hyaloid capillaries and retinal neurons, without interposition of glial cells. Trypan blue and ferrocyanide were not detected within the vitreous humor nor the retina after systemic injection. To this extent, at least, the hyaloid capillaries functionally resemble central nervous system capillaries. Intravascular injections of horseradish peroxidase established the absence of vesicular transfer across the endothelium of the hyaloid capillaries. In addition, quintuple-layered junctions between endothelial cells prevented the intercellular passage of the enzyme. It is likely, therefore, that the only pathway across the endothelium of the hyaloid capillaries is through the plasmalemma of the endothelial cells.